Exclusive breastfeeding: an analysis of the first six months of life (Research, Society and Development, 2022)
Breast milk is considered the best feeding source for infants, being the most economical strategy to reduce infant morbidity and mortality. Objective: To identify the factors that interfere with the exclusive breastfeeding in the first 6 months of the child's life. Method: This is an integrative review of the literature, based on the search for articles published in the Virtual Health Library, Scientific Electronic Library Online and CAPES Journals between 2017 and 2022. Results: It was observed that the main factors that interfere in exclusive breastfeeding are related to maternal age, schooling, family income, psychological, cultural factors and breast problems. Conclusion: Nursing is important to provide support and safety to nursing women. Prenatal consultations are essential to address possible doubts and fears about exclusive breastfeeding, in order to increase the knowledge of breastfeeding women about the harms of early weaning.